Design, synthesis and biological evaluation of erlotinib-based IDO1 inhibitors - Hou, Xi-xi; Gong, Xiao-qing; Mao, Long-fei; Sun, Ge; Yang, Jian-xue (Frontiers in Pharmacology, 2022)
Erlotinib is emerging at the vanguard of therapy for non-small-cell lung cancer (NSCLC) patients with EGFR-activating mutations. However, the increasing therapeutic resistance caused by novel mutations or activated bypass pathways has impaired its performance. Indoleamine 2,3-dioxygenase-1 (IDO1) is a promising cancer therapy target activated in many human cancers including NSCLC. In this study, Erlotinib, was linked to different azide compounds to synthesize a novel class of 1,2,3-triazole ring-containing erlotinib derivatives. Attentive FP prediction model indicated that these compounds were biologically active.Wediscovered that most of the Erlotinib-1,2,3-triazole compounds are capable of suppressing IDO1 activitiesinvitroexperiments.Among them, compound 11b (IC50 = 0.59±0.05 μM) had the strongest inhibitory effect on IDO1.In addition, the antitumor efficacy of compound 11b is comparable to that of erlotinib and IDO1 inhibitor epacadostat in murine tumor models. These data suggest that theerlotinib-1,2,3-triazole compounds are supposed to be more potent than erlotinib against tumourcellswith IDO1 over expression.